2016
DOI: 10.2147/ppa.s110632
|View full text |Cite
|
Sign up to set email alerts
|

Long-term antidepressant use: patient perspectives of benefits and adverse effects

Abstract: Long-term antidepressant treatment has increased and there is evidence of adverse effects; however, little is known about patients’ experiences and views of this form of treatment. This study used mixed methods to examine patients’ views and experiences of long-term antidepressant treatment, including benefits and concerns. Data from 180 patients, who were long-term users of antidepressants (3–15 years), were extracted from an anonymous online survey of patients’ experiences of antidepressants in New Zealand. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
128
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 162 publications
(132 citation statements)
references
References 16 publications
1
128
0
3
Order By: Relevance
“…These practices, if routinely enacted, would help partly explain why the average time a person spends taking antidepressants has doubled in the UK since the guidelines were introduced in 2004,1819 why antidepressant prescriptions are rising overall, and why patients regularly report that their withdrawal is not properly acknowledged, understood, and managed by doctors 2021. In addition, the pooled results of two recent surveys showed that under 2% of around 3000 patients were able to recall being told anything about withdrawal effects, dependence, or potential difficulties in discontinuing treatment 2223…”
mentioning
confidence: 99%
“…These practices, if routinely enacted, would help partly explain why the average time a person spends taking antidepressants has doubled in the UK since the guidelines were introduced in 2004,1819 why antidepressant prescriptions are rising overall, and why patients regularly report that their withdrawal is not properly acknowledged, understood, and managed by doctors 2021. In addition, the pooled results of two recent surveys showed that under 2% of around 3000 patients were able to recall being told anything about withdrawal effects, dependence, or potential difficulties in discontinuing treatment 2223…”
mentioning
confidence: 99%
“…Some patients in mental health care wish to become drug-free after long-term use of psychotropic drugs (1)(2)(3). In Norway, the hospital trusts have been ordered to establish drugfree therapeutic programmes (4).…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon is reported in the scholarly literature (Cartwright et al . ; Hall ; Ostrow et al . ; Read et al .…”
Section: Getting Off Psychotropic Medicationsmentioning
confidence: 99%